Writing a Psychological Horror Play about Loneliness from Childhood Emotional NeglectWriting a Psychological Horror Play about Loneliness from Childhood Emotional Neglect - Jakakul, Monsicha (Siam Communication Review, 2025)
This research aims to study and explore methods for writing a psychological horror play about loneliness from childhood emotional neglect. The researcher began by studying the concept and the characteristics of psychological horror presented in the articles by film and television writer, Jason Hellerman (2024) and film journalist, Ivy Lofberg (2016), as well as the utilization of theatrical elements in horror plays appeared in Emily O'Donnell’s research (2018) with the purpose of exploring the methods for writing a psychological horror play. The researcher studied psychological researches related to loneliness from childhood emotional neglect so as to use the subject matter as the main theme of the play. The knowledge gained was then applied into writing a psychological horror play Wang, with a focus on using the concept and the characteristics of the genre to convey a portrayal of loneliness from childhood emotional neglect and the negative effects of the childhood emotional neglect to the audience. Wang was presented as a staged reading to collect audience’s feedback via questionnaires. The feedbacks show that the audience was able to understand and acknowledge the negative effects of childhood emotional neglect conveyed in the play. However, some audience mentioned that the ambiguity of the narrative and the lack of a clear explanation regarding what the character ‘ghost’ is resulted in the main theme of the play being unclear. Having analyzed the feedbacks, the researcher found the ambiguity to be a distinctive characteristic of the genre that opens the play to the audience’s subjective interpretations. If the researcher were to develop Wang in order to address the issue, the researcher would add actions, as well as dialogues between the characters to strengthen the presentation of the main theme while maintaining the ambiguity of the narrative and the ‘ghost’.